Predictors of behavioral intention to adopt e-AgriFinance app among the farmers in Sarawak, Malaysia - Omar, Quistina; Yap, CS Yap; Ho, P.L.; Keling, William (EMERALD GROUP PUBLISHING LTD, 2022)
Purpose: This study examines the predictors of behavioral intention of farmers to adopt a mobile agricultural finance application called e-AgriFinance using the Unified Theory of Acceptance and Use of Technology (UTAUT) and perceived cost as an additional predictor. Design/methodology/approach: Using a questionnaire survey, data are collected from 337 farmers in Sarawak, Malaysia. The collected data are analyzed using partial least squares structural equation modelling (PLS-SEM). Findings: The research finds that performance expectancy, effort expectancy, social influence and facilitating conditions are positively related to behavioral intention to adopt the e-AgriFinance app, with social influence being the strongest predictor. Perceived cost is also found to be positively related to behavioral intention which contradicts the prediction of the model. Research limitations/implications: This study contributes to the use of UTAUT in predicting the adoption of mobile agricultural finance applications among farmers. Practical implications: For practice, this study provides implications for the Sarawak government to promote digital and financial inclusivity for all communities. This study also provides insights into important features of the e-AgriFinance app for digital finance providers to develop the apps that will be well accepted by farmers in the future. Originality/value: This research is one of the few studies that focused on farmers' mobile technology adoption in agribusiness from the perspective of an emerging economy.